The late-follicular-phase progesterone to retrieved oocytes ratio in normal ovarian responders treated with an antagonist protocol can be used as an index for selecting an embryo transfer strategy and predicting the success rate: a retrospective large-scale study - Zhang, Hongxia; Yang, Shuo; Chen, Lixue; Ma, Caihong; Liu, Ping; Qiao, Jie; Li, Rong (Frontiers in Endocrinology, 2024)
Objective: To determine whether the late-follicular-phase progesterone to retrieved oocytes (P/O) ratio during in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) impacts pregnancy outcomes.12,874 cycles were retrospectively categorized into four groups according to the P/O ratio percentile, with divisions at the 25th, 50th and 75th percentiles.The clinical pregnancy and live birth rates of fresh cycle embryos in Group D were significantly lower than those in the other three groups (45.1% and 39.0%, 43.2% and 37.2%, 39.6% and 33.5%, 33.4% and 28.2% in Group A, B, C, D, respectively; both P < 0.008). Multivariate logistic regression analysis revealed a significant negative correlation between the P/O ratio and live birth, particularly when the P/O ratio was ≥0.22 (OR = 0.862, 95% CI [0.774-0.959], P = 0.006).The P/O ratio has certain predictive value for IVF/ICSI pregnancy outcomes and can be used for decision-making decision regarding fresh embryo transfer.